Тепловіддача бурового інструменту в умовах змінного охолодження - Дреус, Андрій Юлійович (НТУ "ХПІ", 2016)
Предметом дослідження є процеси теплообміну на вибою бурової свердловини при бурінні алмазними коронками. Розглянуто імпульсний режим охолодження, який має місце в нових високоефективних технологіях буріння зі змінною подачею бурового розчину. Методами дослідження є математичне моделювання та обчислювальний експеримент. В роботі представлено результати моделювання гідродинамічних полів на вибою свердловини під час буріння. Запропоновано методику визначення коефіцієнтів тепловіддачі в умовах змінного охолодження. На основі даних по розподілу швидкості розраховані середні коефіцієнти тепловіддачі бурової коронки для різних варіантів змінного режиму охолодження. Результати роботи представляють інтерес для визначення температурного режиму бурового інструменту і визначення енерго- та ресурсозберігаючих режимів буріння з імпульсною промивкою.

The subject of research is the heat transfer process on the working face of the drilling borehole using diamond core bits. This problem is very important for development of new high-technology drilling where variable supply of mud is used. The aim of this article is defining the variable heat transfer coefficients on the drill tool surface. Methods of research are mathematical modeling and computational experiment. Historical review of publications and modern works related at this problem are conducted, and actuality of presented work is justified. The fluid dynamics of drill mud on the working face of borehole is needed for solving thermal problem. Thus, results of 3D modelling of fluid dynamics are presented as well. The outcome of modelling shows that heat transfer coefficient is changed into one direction only. The expressions for defining heat transfer coefficients as function from time were proposed, taking to account a mode of cooling. Based on the calculation of the average mud velocity field, heat transfer coefficients for core bit were defined. Obtained results of interest to determine the temperature regime of drilling tools and determination and energy saving mode with pulse drilling flushing.
Heat transfer of drilling tool under variable cooling
Keywords: буріння; математичне моделювання; CFD технології; промивка; mathematical modelling